(untitled) (Research, Society and Development, 2020)
The objective of this study was to verify the emotional recognition of the child aged five to seven years in institutional care. This is an exploratory qualitative research, carried out using the case study method. Data collection took place between October and November 2016, at a Municipal Reception Center in a municipality in the southwest of Paraná, by means of operational groups, in which the following were used as collection instruments: children’s stories, emoticons and drawings. The difficulty of emotional recognition of children aged five to seven years in institutional care was evidenced, and they describe emotions superficially, showing their difficulties in associating emotions with real events in their lives, indicating difficulty in recognition emotions as their own. However, it should be noted that interest and identification of the children participating in the study prevailed, with stories that addressed negative emotions (sadness, anger and fear). This finding was reinforced during the drafting of the drawings, the children reinforced a greater affinity with negative emotions, since they mostly projected figures that expressed negative feelings in their drawings. This work seeks to contribute to childcare services and other professionals for the need to create moments of expression and emotional recognition in order to provide greater welcome to children’s suffering and possibilities for their re-signification as spaces for promoting children’s mental health.